075 Gadolinium encephalopathy presenting as status epilepticus following intrathecal injection. (23rd August 2021) - Sutherland, Emily; Baird-Gunning, Jonathan; Rudaks, Laura; Palavra, Natalie; Lubomski, Michal; Krause, Martin
Abstract : Objectives: Intra-thecal gadolinium is an alterative contrast agent for computed tomography myelograms. Uncommonly it can cause gadolinium encephalopathy which can present with an array of neurological signs and symptoms. Methods: Review of a case shared by interventional radiology, emergency, neurology and intensive care. This case describes the symptomatology, investigations, and treatment for gadolinium encephalopathy, alongside recommended dosages for intrathecal administration. Results: An 85 year-old female with an allergy to intra-venous iodine presented for a computed tomography myelogram for investigation of bilateral lower limb pain. During the myelogram 8mL of intrathecal gadolinium (Gadovist 1.0) equivalent to 8mmol of gadobuterol was injected in light of the iodine allergy. Ten minutes after completion of the procedure the patient had abrupt onset pelvic pain, nausea, and bilateral lower limb paraesthesiae, which was treated as an allergic reaction with an anti-emetic, analgesia, and steroids. Rapid deterioration followed with extreme agitation and subsequent convulsive status epilepticus. After intubation and treatment with anti-epileptic medication an EEG showed persistent non-convulsive status epilepticus. Intra-venous steroids were introduced, alongside two more anti-epileptics. She was extubated on day 7, and EEG normalised by day 24. The patient was discharged to a rehabilitation hospital with moderate residual cognitive impairments. Conclusion: This case outlines a recognised but infrequently reported response to intrathecal gadolinium. Guidelines for safe intrathecal injection are yet to be identified, as are specific treatment options.